Al-ʿAwāmil wa al-Asykāl fī Taṭawwur al-Dalālah fī al-Lughah al-ʿArabiyyah - luthfi muhyiddin; Ghazali Awaluddin (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2017)
Today, Arabic has become a universal language spoken by more than two billion Arab and non-Arab speakers around the world. It is no longer the language of a particular people but has become a language of many nations. This development has been driven by inventions, innovations, events, ideas, and the emergence of new systems of traditions and norms, all of which require people to understand the concepts and meanings reflected in these developments. Such developments affect every language in terms of both usage and meaning, including the Arabic language. Among the linguistic elements most susceptible to change is vocabulary. Like other contemporary languages, Arabic vocabulary continues to develop over time. Although these changes may not always be noticeable within a single century, they eventually influence both the lexicon and the rules governing the language. The nature of semantic change in Arabic is distinctive. While the language possesses a stable foundation, its branches remain dynamic and capable of development. This research aims to identify the various factors that contribute to semantic change in the Arabic language. The findings indicate the existence of internal.